The Response of Class X IPA SMAN 3 Muaro Jambi Students to the Application of the Jigsaw-Type Cooperative Learning Model in Physics Learning - Astalini Astalini; Dwi Agus Kurniawan; Darmaji Darmaji; Erika Erika; Riko Riko (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2021)
Generally, the learning model used in physics learning is the lecture learning model. The use of a suitable learning model can undoubtedly attract the interest and attention of students. The novelty of this research is the implementation or application of the jigsaw cooperative learning model to determine the students 'responses to the Jigsaw cooperative learning model. This study aims to describe the students' responses to the application of the jigsaw cooperative learning model in physics subjects. The method used is the mixing method (mixture). Quantitative data is obtained by collecting data in the form of a questionnaire. Qualitative data were obtained using an interview instrument sheet. The results showed that 65% (13 of 20 students) responded quite well, and 35% (7 of 20 students) responded well to applying the jigsaw cooperative learning model in physics lessons.